Sistem Pendukung Keputusan Menentukan Siswa Berprestasi dengan Metode SAW (Simple Addtive Weighting) - Isnia Anjar Setyani; Yoannes Romando Sipayung (STMIK Budi Darma, 2023)
MI Kalirejo is an Islamic Madrasah located in Kalirejo Village, East Ungaran District, Semarang Regency. Based on the number of students who have achievement in academic and non-academic fields, a process is needed to determine student achievement. Currently MI Kalirejo still uses the manual method in the assessment process and only through the results of report cards in determining outstanding students. The author is interested in building a website-based decision support system in determining outstanding students based on predetermined criteria, so that it can help make it easier for school institutions to process and determine appropriate, fast and accurate assessments there are several criteria such as the average value of report cards, attitude scores. This system designs and creates and implements a website-based decision support system using the Simple Additive Weighting method. In this study, researchers collected data throught observation and interviews. Then the researchers used the waterfall method in system development. In testing the system using a black box to obtain accuracy results. The conclusions obtained in making a decision support system in determining outstanding students using simple additive weighting based on a website are obtained alternative values from the result of calculations that have been carried out. The author shows accuracy of 100% using the sample and population of Sugiono’s theory. From the result of calculations using the SAW method, it shows that alternative A2 is obtained by a student named Faeza with a value of 1 in the first rank. Thus alternative A2 students on behalf of Faeza were chosen as the best alternative to achieve achievements as outstanding students at MI Kalirejo. Based on the trials and the resulting values have the same result so that the purpose of making this website has been achieved